Comparative Metabolic Profiling of Different Raphanus sativus Cultivars and Their Antioxidant and Anti-Inflammatory Activities - Jae Hyeon Kim; Heeju Kim; Minkuk Park; Byeongjun Park; Beomjune Park; Han Yong Park; Gakyung Lee; Jae Sik Yu (Applied Sciences)
This study investigates the phytochemical composition of the aerial parts of three radish cultivars: KR 391, KR CheongHong, and KR 407, named RL1, RL2, and RL3, respectively, using UPLC–Orbitrap–MS to profile the secondary metabolites. The secondary metabolites were characterized to provide a comprehensive overview of their diversity and bioactivity. Multivariate analysis revealed cultivar-specific variations in metabolite profiles and tentatively identified 22 metabolites, which include 17 flavonoids and five phenolics. The extracts of the radish cultivars were tested for their cytotoxicity, antioxidant activity measured with a DPPH assay, and anti-inflammatory activity measured by NO production. The findings highlight the pharmaceutical potential of radish aerial parts and provide insights into the relationship between metabolite composition and biological activity, contributing to their value in health-promoting applications.